PENGARUH PROGRAM KERINGANAN DAN SOSIALISASI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (STUDI PADA SAMSAT MINAHASA) - Sovia Lara; Jaqueline E.M. Tangkau; Pricilia J. Pesak (STIE PGRI Dewantara Jombang, 2024)
This study aims to analyze the influence of motor vehicle tax relief programs, taxpayer awareness, tax socialization, and service quality on taxpayer compliance at the Samsat Minahasa Office. The research employed a quantitative approach using a survey method and multiple linear regression analysis. The population consisted of registered motor vehicle taxpayers, while a sample of 65 respondents was determined using the Slovin formula with a 10% significance level and purposive sampling technique. Data were collected through a structured questionnaire and analyzed using SPSS version 30. The results indicate that tax relief programs, tax socialization, and service quality have a positive and significant effect on taxpayer compliance. In contrast, taxpayer awareness does not significantly influence compliance. The coefficient of determination (R²) of 0.547 shows that 54.7% of the variance in taxpayer compliance is explained by the four independent variables, while the remaining 45.3% is influenced by other factors outside the research model.